Development of Project Based Learning E-Module on Salt Hydrolysis Material to Improve Student Learning Outcomes - Nopita; Raudhatul Fadhilah; Tuti Kurniati; Hamdil Mukhlishin (Postgraduate, University of Mataram, 2024)
The conventional printed modules used in schools have not been able to make students active and understand chemical concepts. Therefore, it is necessary to develop an interactive multimedia-based e-module grounded in Project Based Learning (PjBL), equipped with videos, images, and interactions to engage students and facilitate easier comprehension of chemical materials. The iam of this study is to improve the learning outcomes of class XI Science Muhammadiyah 1 High School Pontianak. The method used in this research is development (research and development) employing the ADDIE model, which includes the stages of (analysis, design, development, implementation, and evaluation). The research findings indicate very high criteria with an average validity coefficient of 0.93 for each aspect of media, materials, and language. The practicality analysis, based on the response questionnaires from the small group trial and the main field trial, showed practicality values of 71% and 74%, respectively, both with practical criteria. It can be concluded that the project based learning e-module developed is feasible to be used as an effective and practical learning tool for XI Science students and chemistry teachers in high schools.